Obszary lokalnej polityki gospodarczej - Sztando, Andrzej (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The article covers the issues of the local government influence on the economic subjects. The aim of the article is to identify, define and characterize those parts of local governments' policies, which result in the change of the conditions for running the business activity. In the initial part of the article, the author defines the idea of the local government economic policy area. The following issue being characterized is the definition of the spatial policy area, budget policy area, ecological policy area, infrastructure policy area, the area of the economic activity policy, the area of the commune's property management policy, educational policy area, internal policy area and the area of the information management policy. The author nurtures the hope that it will contribute to the development of the theoretical base of the actions supporting the economic development of the communes and that it will also contribute to the increase of the interest for these issues. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 232-243